Osteopontin, CD44, and NFκB Expression in Gastric Adenocarcinoma - Kim, Jung Yeon; Bae, Byung-Noe; Kim, Kyoung Soo; Shin, Eunah; Park, Kyeongmee (Cancer research and treatment, 2009)
Purpose ; Osteopontin (OPN) binds to CD44 and nuclear factor-κB (NFκB) and OPN mediates tumorigenesis, invasion and metastasis, but the interrelationships between OPN, CD44 and NFκB are not fully understood, and especially in gastric carcinogenesis. We examined the expressions of OPN, CD44, and NFκB in untreated gastric adenocarcinomas. Materials and Methods ; The materials from 211 cases of gastric adenocarcinoma were immunostained for OPN, CD44 and NFκB by using a tissue microarray. The OPN mRNA expression was measured in 10 cases by performing real-time RT-PCR. Results ; The expression of OPN, CD44 and NFκB was noted in 61.7%, 11.4% and 26.6% of the adenocarcinoma tissues, respectively. No significant correlation was detected among the expressions of these proteins. The OPN protein expression was negatively correlated with angioinvasion (p<0.05) and patient survival (p<0.05), whereas the CD44 and NFκB protein expressions were not correlated with any of the clinicopathological factors we examined. The depth of invasion, lymph node status and perineural invasions were rognostic factors based on the Cox analysis. The OPN mRNA expression showed no significant difference between the adenocarcinoma and the paired normal mucosa on real-time RT-PCR. Conclusion ; OPN may have a currently undetermined role in gastric carcinogenesis, and CD44 and NF κB may have minor roles in gastric adenocarcinoma. Purpose ; Osteopontin (OPN) binds to CD44 and nuclear factor-κB (NFκB) and OPN mediates tumorigenesis, invasion and metastasis, but the interrelationships between OPN, CD44 and NFκB are not fully understood, and especially in gastric carcinogenesis. We examined the expressions of OPN, CD44, and NFκB in untreated gastric adenocarcinomas. Materials and Methods ; The materials from 211 cases of gastric adenocarcinoma were immunostained for OPN, CD44 and NFκB by using a tissue microarray. The OPN mRNA expression was measured in 10 cases by performing real-time RT-PCR. Results ; The expression of OPN, CD44 and NFκB was noted in 61.7%, 11.4% and 26.6% of the adenocarcinoma tissues, respectively. No significant correlation was detected among the expressions of these proteins. The OPN protein expression was negatively correlated with angioinvasion (p<0.05) and patient survival (p<0.05), whereas the CD44 and NFκB protein expressions were not correlated with any of the clinicopathological factors we examined. The depth of invasion, lymph node status and perineural invasions were rognostic factors based on the Cox analysis. The OPN mRNA expression showed no significant difference between the adenocarcinoma and the paired normal mucosa on real-time RT-PCR. Conclusion ; OPN may have a currently undetermined role in gastric carcinogenesis, and CD44 and NF κB may have minor roles in gastric adenocarcinoma. KCI Citation Count: 4